Penerapan Model Concept Sentence untuk Meningkatkan Keterampilan Menulis Karangan Narasi Siswa - Shofia Salsabila; Asis Saefuddin; Heri Hidayat (Mitra PGMI: Jurnal Kependidikan MI, 2021)
This research was motivated by a lack of students' vocabularies so that they have difficulty narrating ideas into their writing. Students also often repeated the same words and used the local language. The purpose of this study was to determine students' narrative essay writing skills before the use of the concept sentence model, as well as student's learning activities using the concept sentence model at MI Al-Khoiriyyah III Garut Regency. This research was a Classroom Action Research consisted of two cycles. The results showed the activities of students before the concept sentence model was still lacking (43.04%), and the average of learning outcomes was only (48.69). The use of the concept sentence model run according to its stages, the activities, and students' learning outcomes have increased in every cycle. In the first cycle, the students' activities reached 66.85% and then increased in the second cycle by 78.81%. While students' learning outcomes in the first cycle of action I reached 62.82 then increased in action II by 69.35. As for the second cycle of action I students' learning outcomes reached 75, and for the action II reached 82.61 by very good criteria.